An Accurate Phase Interface Locating Algorithm for Pore-Scale Two-Phase Interfacial Flows. (10th April 2023) - Mei, Qiliang; Wu, Tianjiang; Li, Chao; Zhou, Xiaoying
Abstract : Direct numerical simulation of pore-scale flow in porous media at pore scale is a fast developing technique to investigate pore-scale flow behaviors. However, with the decrease of the spatial scale, the interfacial tension of the two-phase interface will have an important impact on the two-phase flow processes. As a result, spurious currents near the interface with this method have an important impact on the numerical accuracy and computational efficiency, seriously affecting the numerical prediction of pore-scale fluid flow. Ghost cell method can greatly reduce the spurious currents near the interface, but it needs to locate the phase interface accurately. In this work, a new method using constant velocity spiral to approximate the two-phase interface is proposed. The method not only considers the curvature of the phase interface but also considers the influence of the curvature change on the phase interface, which greatly improves the ability of the phase interface position. The new method can improve the accuracy of interfacial tension treatment and then improve the prediction ability of volume of fluid in high interfacial tension driven flow. Numerical simulations of capillary rising, droplet spreading on a plane, and bubble rising show that the method is accurate and has a strong engineering application prospect.